Understanding Regulatory Fit - Aaker, Jennifer L.; Lee, Angela Y. (Journal of Marketing Research, 2006)
The authors focus on three critical areas of future research on regulatory fit. First, they focus on how regulatory orientation is sustained. The authors argue that there are two distinct approaches that bring about the “just-right feeling”: (1) a process-based approach that involves the interaction between regulatory orientation and decision-making processes and (2) an outcome-based approach that involves the interaction between regulatory orientation and the framed outcomes offered. Second, the authors discuss possible boundary conditions of regulatory fit effects, highlighting the apparent paradoxical role of involvement. They suggest that the antecedents that give rise to regulatory fit (e.g., lowered motivation) can differ from its consequences (e.g., increased motivation). Third, the authors discuss broader implications of regulatory fit, proposing three possible mechanisms by which regulatory fit can lead to improved physical health and discussing the degree to which the just-right feeling plays a role in goal-sustaining experiences related to subjective well-being (e.g., flow).